Terms of Court at Albuquerque, Roswell, Las Vegas, Silver City, and Las Cruces, N.Mex.: hearings before the United States House Committee on the Judiciary, Subcommittee No. 3 (Judiciary), Sixty-Eighth Congress, first session, on Apr. 18, 1924. - United States. (U.S. G.P.O., 1924)
Considers (68) H.R. 7523
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part II
Considers (68) H.R. 7523
Committee Serial No. 31
Keywords: Court calendars / New Mexico.; District courts / New Mexico.